Distal mutation V486M disrupts the catalytic activity of DPP4 by affecting the flap of the propeller domain - Li Teng-teng; Peng Cheng; Wang Ji-qiu; Xu Zhi-jian; Su Ming-bo; Li Jia; Zhu Wei-liang; Li Jing-ya (Acta Pharmacologica Sinica; Vol 43, No 8 (August 2022): Acta Pharmacologica Sinica, 2022)
Dipeptidyl peptidase-4 (DPP4) plays a crucial role in regulating the bioactivity of glucagon-like peptide-1 (GLP-1) that enhances insulin secretion and pancreatic β-cell proliferation, making it a therapeutic target for type 2 diabetes. Although the crystal structure of DPP4 has been determined, its structure-function mechanism is largely unknown. Here, we examined the biochemical properties of sporadic human DPP4 mutations distal from its catalytic site, among which V486M ablates DPP4 dimerization and causes loss of enzymatic activity. Unbiased molecular dynamics simulations revealed that the distal V486M mutation induces a local conformational collapse in a β-propeller loop (residues 234–260, defined as the flap) and disrupts the dimerization of DPP4. The “open/closed” conformational transitions of the flap whereby capping the active site, are involved in the enzymatic activity of DPP4. Further site-directed mutagenesis guided by theoretical predictions verified the importance of the conformational dynamics of the flap for the enzymatic activity of DPP4. Therefore, the current studies that combined theoretical modeling and experimental identification, provide important insights into the biological function of DPP4 and allow for the evaluation of directed DPP4 genetic mutations before initiating clinical applications and drug development.